Investigation the influence of structure parameters on giant-magnetoimpedance effect measured by non-contact method. Issue 6 (11th October 2020) - Feng, Zhu; Zhi, Shaotao; Sun, Xuecheng; Yan, Lili; Liu, Cui; Lei, Chong
Abstract : Purpose: This paper aims to investigate the influence of structure parameters on giant-magnetoimpedance (GMI) effect measured by non-contact method. Design/methodology/approach: The GMI sensor contains a Co-based internal magnetic core fabricated by laser cutting and an external solenoid. The influences of magnetic permeability of magnetic core and structure parameters on GMI effect were calculated in theoretical model. The output impedance, resistance, reactance and GMI ratio were measured by non-contact method using impedance analyzer. Findings: Enhancing external magnetic field intensity can decrease the magnetic permeability of core, which has vital influences on the magnetic property and the output response of GMI sensor. In addition, increasing the width of magnetic core and the number of solenoid turns can increase the maximum GMI ratio. The maximum GMI ratio is 3, 230% with core width of 6 mm and solenoid turns of 200. Originality/value: Comparing with traditional contact-measured GMI sensor, the maximum GMI ratio and the magnetic field sensitivity are improved and the power consumption is decreased in non-contact measured GMI sensor. GMI sensor measured by non-contact method has a wide range of potential applications in ultra-sensitive magnetic field detection.